Kontribusi Wakaf dalam Mewujudkan Kesejahteraan Sosial, Ekonomi, dan Pendidikan di Indonesia - Maryam Qurotul Aini, Siti; Syahda, Alifia; Roikhatul Jannah, Diana Dewi (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Waqf plays a strategic role in various aspects of life, particularly in the social, economic, and educational sectors. This study explores the contribution of waqf as an instrument to achieve equitable welfare for society, especially for underprivileged groups. Properly managed waqf assets have demonstrated significant impacts in establishing and developing educational institutions, such as universities and Islamic boarding schools, which contribute to improving human resource quality. Additionally, waqf helps reduce the dependency of impoverished communities on state assistance through the productive management of assets. This article highlights the importance of competent and prudent nadhir (waqf managers) in managing waqf assets so that their benefits can be widely distributed regardless of social status. With optimal management, waqf can serve as a solution for creating inclusive and sustainable social welfare.